2018
DOI: 10.4236/ajibm.2018.82021
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Information Technology on the Supply Chain Performance of the Car Segmentation Companies with Emphasis on the Integrity and Flexibility

Abstract: Companies are struggling in a highly competitive environment to accelerate their operations and operations. Discussions such as globalization and the expansion of networks such as the Internet are important issues that affect the resources, marketing, and other issues that companies engage with. The effects of information technology in industries, in the supply chain areas and in the value chain, are evident from the relationship with suppliers to production and communication with customers, including the impa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…From previous studies it was confirmed that there is a positive correlation between SC agility and performance (Betts and Tadisina, 2009;Alkrait and Almaktoom, 2021;Loury-Okoumba and Mafini, 2021); SC resilience and SC performance (Kariuki et al, 2018;Chowdhury et al, 2019); IT capabilities and SC performance (Wu et al, 2006;Niu, 2010;Mashreghi et al, 2018). Similarly, SC agility (Alkrait and Almaktoom, 2021), SC resilience (Kariuki et al, 2018) and IT capability (Niu, 2010;Mashreghi et al, 2018) have significant influence on SC performance. SC agility and SC resilience have a positive and significant relationship with SC performance (Carvalho et al, 2012).…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…From previous studies it was confirmed that there is a positive correlation between SC agility and performance (Betts and Tadisina, 2009;Alkrait and Almaktoom, 2021;Loury-Okoumba and Mafini, 2021); SC resilience and SC performance (Kariuki et al, 2018;Chowdhury et al, 2019); IT capabilities and SC performance (Wu et al, 2006;Niu, 2010;Mashreghi et al, 2018). Similarly, SC agility (Alkrait and Almaktoom, 2021), SC resilience (Kariuki et al, 2018) and IT capability (Niu, 2010;Mashreghi et al, 2018) have significant influence on SC performance. SC agility and SC resilience have a positive and significant relationship with SC performance (Carvalho et al, 2012).…”
Section: Discussionmentioning
confidence: 80%
“…Research has shown that IT capabilities and SC agility (Liu et al, 2013;Hepburn et al, 2020); and SC agility and SC resilience (Altay et al, 2018) have a considerable impact on SC performance in uncertain circumstances (Liu et al, 2013;Hepburn et al, 2020). From previous studies it was confirmed that there is a positive correlation between SC agility and performance (Betts and Tadisina, 2009;Alkrait and Almaktoom, 2021;Loury-Okoumba and Mafini, 2021); SC resilience and SC performance (Kariuki et al, 2018;Chowdhury et al, 2019); IT capabilities and SC performance (Wu et al, 2006;Niu, 2010;Mashreghi et al, 2018). Similarly, SC agility (Alkrait and Almaktoom, 2021), SC resilience (Kariuki et al, 2018) and IT capability (Niu, 2010;Mashreghi et al, 2018) have significant influence on SC performance.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…There is a positive significant relationship between learning and supply chain integration, emphasizing the importance of continuous learning in achieving supply chain integration (Khan & Wisner, 2019). The impact of information technology on supply chain performance has been studied, highlighting the importance of finding information technology in the supply chain and its positive impacts on supply chain variables (Mashreghi et al, 2018). Insider "supply chain" knowledge has been identified as a key facet in the theft of livestock, emphasizing the importance of understanding and managing information within the supply chain (Smith, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%